2022
DOI: 10.3389/fmed.2022.909330
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Air Pollution on the Ocular Surface and Tear Cytokine Levels: A Multicenter Prospective Cohort Study

Abstract: PurposeTo assess air pollution-induced changes on ocular surface and tear cytokine levels.MethodsAs a prospective multicenter cohort study, 387 dry eye disease (DED) participants were recruited from five provinces in China and underwent measurements of ocular surface disease index (OSDI), Schirmer’s I test (ST), tear meniscus height (TMH), tear film break-up time (TBUT), corneal fluorescein staining (CFS), meibomian gland (MG) function, and tear cytokines. The associations between ocular surface parameters and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…All included articles and the identified SDoH in each study are summarized in Table 1. Dry eye/ocular surface [18 ▪▪ ,19 ▪ –38 ▪ ] (21 articles) was the most prevalent cornea condition, followed by pterygium [39 ▪▪ ,40 ▪ –42 ▪ ] (4 articles), keratoplasty [43 ▪▪ ,44–46] (four articles), keratoconus [47 ▪ ,48,49] (three articles), cornea donation [50,51 ▪▪ ,52 ▪▪ ] (three articles), cornea thickness [53 ▪ ,54 ▪ ] (two articles), trachoma [55 ▪▪ ,56] (two articles), corneal ulcers [57 ▪ ,58 ▪ ] (two articles), corneal arcus [59 ▪ ] (one article), and corneal opacity[60 ▪ ] (one article). Cornea donation for transplantation was also explored.…”
Section: Search Results and Studies Included In The Reviewmentioning
confidence: 99%
“…All included articles and the identified SDoH in each study are summarized in Table 1. Dry eye/ocular surface [18 ▪▪ ,19 ▪ –38 ▪ ] (21 articles) was the most prevalent cornea condition, followed by pterygium [39 ▪▪ ,40 ▪ –42 ▪ ] (4 articles), keratoplasty [43 ▪▪ ,44–46] (four articles), keratoconus [47 ▪ ,48,49] (three articles), cornea donation [50,51 ▪▪ ,52 ▪▪ ] (three articles), cornea thickness [53 ▪ ,54 ▪ ] (two articles), trachoma [55 ▪▪ ,56] (two articles), corneal ulcers [57 ▪ ,58 ▪ ] (two articles), corneal arcus [59 ▪ ] (one article), and corneal opacity[60 ▪ ] (one article). Cornea donation for transplantation was also explored.…”
Section: Search Results and Studies Included In The Reviewmentioning
confidence: 99%
“…In recent years, particulate matter (PM)-induced DED has become a dramatic health concern worldwide 1 , 2 . According to the World Health Organization, PM, O 3 , NO 2 , and SO 2 are the most significant pollutants 25 . Our study, for the first time, evaluated the links among air pollutants (PM 10 , PM 2.5 , CO, O 3 , NO 2 , and SO 2 ), meteorological parameters (AP, AT, WS, PR, RH, and AV) and the clinical characteristics of DED in cold regions of China.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 23922 ophthalmic outpatients recruited from 23 cities, in China in 2013 shown that SO 2 was identified as the risk factors for DED [30]. A prospective multicenter cohort study of 387 subjects in China found that exposure to SO 2 was positively associated with decreased OSDI and TBUT scores, resulting in ocular sensitivity and irritation [15]. A Korean study of 16431 individuals using a nationally representative sample found that SO 2 was associated with DED, while CO were not [31].…”
Section: Ded and Other Gaseous Pollutantsmentioning
confidence: 99%